Implementasi sistem informasi berbasis web menggunakan model RAD (CV indo karyatama perkasa somagede) - Nardi Riana, Septi; Anggoro, Tri (Journal of Computer Science and Informatics Engineering, 2025)
The current strategy of several companies from small to large scale is to utilize web-based technology for promotional media so that it is not limited by space and time, therefore the author plans to implement a web-based information system using the RAD method for CV Indo Karyatama Perkasa because This CV is a start-up in the advertising sector that does not yet have a website for promotional media and services so that it can capture a wider market share. Flowcharts as a design model and black box testing are used as a medium for testing the work results of the system. This research will produce an information system regarding CV Indo Karyatama Perkasa.